2021
DOI: 10.1158/1078-0432.ccr-21-2863
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A Harboring Leukemia-Associated Mutations Directs Sensitivity to DNA Damage at Replication Forks

Abstract: Purpose: In acute myeloid leukemia (AML), recurrent DNA methyltransferase 3A (DNMT3A) mutations are associated with chemoresistance and poor prognosis, especially in advanced-age patients. Gene-expression studies in DNMT3A-mutated cells identified signatures implicated in deregulated DNA damage response and replication fork integrity, suggesting sensitivity to replication stress. Here, we tested whether pharmacologically induced replication fork stalling, such as with cytarabine, creates a th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Among them, small-molecule inhibitor-targeted treatment is even more popular and highly concerned. Small molecule inhibitor-targeted treatment mainly suppresses cell growth, proliferation, and survival by targeting relevant cell signaling pathways (for example, kinase pathway, apoptosis pathway, DNA damage repair-related pathway) to achieve the effect of treating AML [ 44 47 ]. At present, the research of such new therapies has also achieved gratifying results.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, small-molecule inhibitor-targeted treatment is even more popular and highly concerned. Small molecule inhibitor-targeted treatment mainly suppresses cell growth, proliferation, and survival by targeting relevant cell signaling pathways (for example, kinase pathway, apoptosis pathway, DNA damage repair-related pathway) to achieve the effect of treating AML [ 44 47 ]. At present, the research of such new therapies has also achieved gratifying results.…”
Section: Discussionmentioning
confidence: 99%
“…Mutationally VR_C4 like VSC had high mutation rates in FLT3 and NPM1 , but also in DNMT3A unlike VSC. Mutations in DNMT3A may be associated with better response to AZA and cytarabine 40,41 . Thus VR_C4-like tumors may still benefit from current VEN combination therapies and perhaps with some selectively targeting DNMT3 inhibitors 42 .…”
Section: Discussionmentioning
confidence: 99%
“…We reported that DNMT3A-deficient cells favor HR/c-NHEJ, owing to the downregulation of PARP1 and the reduction of a-NHEJ [ 85 ]. In addition, a recent study has reported that DNMT3A -mutated leukemia cells exhibit impaired PARP1 recruitment, p53 activation and increased DNA damage after being challenged by replication stress-induced medications [ 108 ]. Consequently, DNMT3A-deficient leukemia cells are resistant to PARPi.…”
Section: Pre-existing Resistance To Parpi: Tumor-inducing Mutationsmentioning
confidence: 99%